#TITLE_ALTERNATIVE# - IHROMI (NIM : 25612001), HAFIDH
City development is pro automobile industries these days. This has led to a motorcar-dependent society in big cities. This high reliance on motorcars causes negative effects on people's lives such as reducing physical activity, lowering air quality, and other serious health problem. On the other hand, cities are now required to be walkable in order to be desirable for it's people. Since walkability is a qualitative concept with subjective value it's vague to determine whether or not a city environment is walkable. Walkability needs to be redefined to be more clear and objective. This thesis evaluates walkability in a city center neighborhood objectively refering to IPEN’s (International Physical Activity and the Environment Network) mathematical approach modeled in City Engine which is a 3D parametric modeling software based on rule based modeling. Using this software, IPEN’s approach on walkability can be modeled so that evaluating walkability using IPEN method can be done with ease. The research object of this thesis is Bandung’s city center neighborhood. In this thesis, the object is divided into smaller parts to be evaluated each of the part’s walkability index so that the walkability index of each part known and then compared. This analysis shows that part of the city that has the most commercial retail facility has a higher walkability index compared to the other part of the city. Based on the analysis, the simulation stage is conducted to further explore the nature of walkability with IPEN’s mathematical approach. This simulation suggests that the factor that has the most effect on walkability is the quality of connectivity within a given city neighborhood, the more circulation path a neighborhood has, the better it’s walkability. This mathematical evaluation method developed by IPEN gives a more objective and clear result on walkability in Bandung city center.